MEMS-Based Endoscopic Optical Coherence Tomography - Jingjing Sun; Huikai Xie (International Journal of Optics)
Early cancer detection has been playing an important role in reducing cancer mortality. Optical coherence tomography (OCT), due to its micron-scale resolution, has the ability to detect cancerous tissues at their early stages. For internal organs, endoscopic probes are needed as the penetration depth of OCT is about 1–3 mm. MEMS technology has the advantages of fast speed, small size, and low cost, and it has been widely used as the scanning engine in endoscopic OCT probes. Research results have shown great potential for OCT in endoscopic imaging by incorporating MEMS scanning mirrors. Various MEMS-OCT designs are introduced, and their imaging results are reviewed in the paper.